Evaluating the Therapeutic Efficacy of rTMS Combined with Low-Dose Antipsychotic Medication in Somatic Symptom Disorder - Wu J; Wang T; Jiang X (Neuropsychiatric Disease and Treatment)
Jinbo Wu,1 Tingting Wang,2 Xiaomei Jiang1 1Department of Psychiatry, The First Affiliated Hospital of Harbin Medical University, Harbin, Heilongjiang, 150001, People’s Republic of China; 2Department of Endocrinology, Harbin Red Cross Central Hospital, Harbin, Heilongjiang, 150070, People’s Republic of ChinaCorrespondence: Jinbo Wu, Department of Psychiatry, The First Affiliated Hospital of Harbin Medical University, No. 23 Youzheng Street, Harbin, 150001, Heilongjiang, People’s Republic of China, Tel +86-0451-85553553, Email tianwenyi526149@163.comObjective: We aim to evaluate the therapeutic efficacy of repetitive transcranial magnetic stimulation (rTMS) combined with low-dose antipsychotic medication in somatic symptom disorder (SSD) and its effects on neurotransmitters and inflammatory factors.Methods: This was a retrospective study. According to different treatment regimens, 90 patients with SSD were divided into a medication group (n = 45) and a combination group (n = 45). The medication group received low-dose antipsychotic medication, while the combination group received low-dose antipsychotic medication combined with rTMS. The primary outcomes were to compare the scores of the Hamilton Anxiety Rating Scale (HAMA) and the Hamilton Rating Scale for Depression (HAMD) between the two groups before and after intervention. The secondary outcomes involved assessing the quality of life of the two groups using the Medical Outcomes Study 36-Item Short Form Health Survey (SF-36). Neurotransmitters and inflammatory factors were measured using enzyme-linked immunosorbent assay. Clinical efficacy and adverse reaction rates were also compared.Results: After treatment, the combination group showed greater improvements in HAMA and HAMD scores, higher SF-36 scores across physical, social, psychological, and daily living dimensions, with increased levels of γ-aminobutyric acid and 5-hydroxytryptamine, decreased dopamine, lower levels of C-reactive protein and interleukin-1β, higher interleukin-10 levels (all P < 0.05). The total effective rate of the combination group was 97.78%, higher than that of the medication group at 84.44% (P = 0.024). There was no significant difference in the incidence of adverse reactions between the two groups (P > 0.05).Conclusion: rTMS combined with low-dose antipsychotic medication for SSD shows superiority over medication alone in improving anxiety and depression, enhancing quality of life, regulating neurotransmitter levels, and reducing inflammatory factors, with fewer side effects and significant clinical efficacy. However, due to the small sample size of this study, further prospective, randomized controlled studies with larger samples are needed.Plain Language Summary: Given the limited efficacy of existing treatments for schizophrenia spectrum disorders (SSD), this study aimed to assess whether combining repetitive transcranial magnetic stimulation (rTMS) with low-dose antipsychotic medication could enhance therapeutic outcomes. By analyzing symptom relief, neuromediator regulation, inflammatory response reduction, and quality-of-life improvements in SSD patients, the results demonstrated that this combined approach outperformed antipsychotic monotherapy. These findings imply that rTMS-antipsychotic combination therapy may represent a viable, innovative treatment option for clinical practice, potentially addressing unmet needs in SSD management.Keywords: somatic symptom disorder, repetitive transcranial magnetic stimulation, antipsychotic medication, clinical efficacy, neurotransmitters, inflammatory factors